Secondary prophylaxis vs. on‐demand treatment to improve quality of life in severe adult haemophilia A patients: a prospective study in a single centre. Issue 1 (27th June 2013) - Aznar, J. A.; García‐Dasí, M.; Pérez‐Alenda, S.; Marco, A.; Jaca, M.; Moret, A.; Querol, F.
<x xml:space="preserve">Abstract</x> Background Retrospective publications show a decrease in the bleeding frequency and an improvement in the quality of life (QoL) in severe adult haemophilia A (SAHA) after switching from the on‐demand treatment (DT) to secondary prophylaxis (SP). But there are no prospective studies which demonstrate, using a haemophilia‐specific questionnaire, an improvement in the QoL after such treatment change. The main objective of this study is to prospectively compare the QoL and the musculoskeletal assessment after switching from DT to SP in SAHA using the A36 Hemofilia‐QoL®. As secondary objective, we compare the haemarthrosis frequency and factor VIII consumption in DT and SP during a similar period of time (12 months) after switching. Materials and Methods We have designed a prospective study including SAHA who have been under DT and were changed to a protocol, which combines SP (biweekly administration of factor VIII) with individualized physiotherapy programme. Results Twelve months after switching to SP, the QoL was significantly improved (P = 0·005). Musculoskeletal assessment of pathologic irreversible joints and joints with a reversible alteration was generally improved, although in only a few joints, this improvement was statistically significant. Haemarthrosis was strongly reduced (12·60–1·42, P < 0·001). Conclusions This prospective study has demonstrated a statistically significant improvement in the QoL after 1 year from switching patients from DT to SP. The musculoskeletal assessment after 1 year was maintained similar or slightly improved. When we compared retrospective DT and prospective SP, haemarthrosis where strongly reduced requiring a slight increase in the consumption of factor VIII concentrates.